Тechnique for growth of CSI:TL crystals with internal radioisotope for nuclear physics - Shpilinskaya, A.L.; Kudin, A.M.; Kolesnikov, А.V.; Didenko, A.V.; Kudin, K.A. (Вопросы атомной науки и техники, 2018)
CsI:Tl crystals have been grown by Stockbarger technique in sealed quartz ampoules. Grown ingots do not adhere to the material of the container. Ready crystals have no residual stresses and do not break during subsequent mechanic treatment. Vibration absorption of grown crystals contains no bands of OH⁻ or CO²⁻₃ ions in the IR region. After irradiation the electronic absorption has no bands of F- or FA-color centers in the visible region. Spectrometric characteristics of the grown crystals are not inferior to standard. Developed technique is recommended for growth of CsI:Tl scintillation material with internal source of radiation. The peculiarity of the method is the dehydration of raw material at T ⩽ 40°C under conditions which exclude photolysis of salt.